2020
DOI: 10.3390/cells9040816
|View full text |Cite
|
Sign up to set email alerts
|

Lamin Mutations Cause Increased YAP Nuclear Entry in Muscle Stem Cells

Abstract: Mutations in the LMNA gene, encoding the nuclear envelope A-type lamins, are responsible for muscular dystrophies, the most severe form being the LMNA-related congenital muscular dystrophy (L-CMD), with severe defects in myonucleus integrity. We previously reported that L-CMD mutations compromise the ability of muscle stem cells to modulate the yes-associated protein (YAP), a pivotal factor in mechanotransduction and myogenesis. Here, we investigated the intrinsic mechanisms by which lamins influence YAP subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Interestingly, sustained Taz upregulation enhances terminal differentiation of myoblasts in vitro and in vivo [87][88][89]. Yap was recently shown to contribute to the pathogenesis in muscular dystrophy, as increased nuclear localization of Yap is seen in lamin-A-related congenital muscular dystrophy (L-CMD) [90]. Our analysis also revealed significant upregulation of Yap expression and activity along with upregulation of several other pathways' components in the EDMD-causing emerin mutants, suggesting there is increased Yap localization in the nucleus that promotes proliferation activity and inhibits the differentiation program [83].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sustained Taz upregulation enhances terminal differentiation of myoblasts in vitro and in vivo [87][88][89]. Yap was recently shown to contribute to the pathogenesis in muscular dystrophy, as increased nuclear localization of Yap is seen in lamin-A-related congenital muscular dystrophy (L-CMD) [90]. Our analysis also revealed significant upregulation of Yap expression and activity along with upregulation of several other pathways' components in the EDMD-causing emerin mutants, suggesting there is increased Yap localization in the nucleus that promotes proliferation activity and inhibits the differentiation program [83].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to YAP response, our results also indicated that lamin A/C ratio 42,43 44 , which would be a natural next step of investigation. Our study therefore provides insights into the mechanistic regulation of epithelial monolayers to large-scale substrate curvature, with potential impact for a large number of physiological situations, given the ubiquitous presence of curvature in vivo.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, atrial cardiac defect-affected myofibroblasts showed reduction of both emerin and SUN2 proteins, supposed to cause the reduced formation of F-actin stress fibers in cyclic stretches condition [244]. Moreover, the same YAP nuclear accumulation previously reported in mutant lamins has been revealed in congenital myopathy with a mutation in nesprin-1 protein [237]. The common element to all the laminopathies would thus appear to be deregulated cell functionality induced by impaired mechanotransduction.…”
Section: Lamin A/c Mechanotransduction In Laminopathiesmentioning
confidence: 67%
“…On the other hand, the lamina pathological activity affects the translocation of nuclear molecules, as demonstrated in congenital muscular dystrophy, where its impaired sensitivity causes an altered activation of YAP signaling [8,143]. Congenital muscular dystrophy-related cells have been correlated to increased YAP nuclear localization due to increased nuclear import, induced by nuclear envelope defect [237]. Likewise, EDMD mice models show enhanced nuclear translocation of activated extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK).…”
Section: Lamin A/c Mechanotransduction In Laminopathiesmentioning
confidence: 99%